The role of Arab and Muslim scientists in developing of mathematics - Al-Thubaiti, Yasser Abdullah; Al Maghamsi, Fawzia Dhawaihr (Arab Journal for Sciences and Research Publishing, 2016)
The article aimed to clarify the history of Arab and Muslim mathematicians and to clarify the most important scientific achievements that played an active role in the development of mathematics. The descriptive research was followed through research in scientific encyclopedias such as the Encyclopedia of Mathematics and related scientific references. The history of mathematicians from ancient times to the twentieth century was studied and the most important mathematicians who had clear and documented scientific achievements were emphasized. The article concluded that there is a great role for the Arab and Muslim scientists in establishing the mathematics of this age, which expressed complex and logical relations, and provided us with a framework to regulate the large amounts of information and data by computer. The researchers recommended the need to document the work of Arab and Muslim scientists in scientific encyclopedias in various fields .
Keywords: scientists; Arabs; Muslims; mathematics